Mechanical and Failure Analysis of Multi-Materials Adhesive Joining - Dias, Gimash Kavishka; Sakundarini, Novita; May May, Christina Chin (International Journal of Integrated Engineering, 2021)
The evolvement of joining dissimilar materials using adhesive joining has been vastly improved over the years and has been used in various industries such as medical, automotive and construction. In the automotive industry specifically, the use of multi-materials has proven to improve material properties. However, fewer studies have been done to understand the failure mechanism of multi-material adhesive joining. This study investigates the mechanical failure for lap joints of different materials that have undergone mechanical abrasive treatments and chemical etching, before adhesively joined together. The result showed that sandblasting as surface preparation is very important as it increases the surface roughness of the material, giving a better adhesion bond. Chemical etching also increases the surface roughness minutely and is considered an important step for the purpose of degreasing. Tensile tests were conducted as a destructive test and it was found that mild steel, aluminum, and PVC materials were deemed to be the best choice for multi materials adhesive joining. Multi-material, Failure analysis, Adhesive joining, Automotive